Key Aspects of Digital Transformation Towards Building Fourth Generation Universities in Algeria (Journal of Economic Additions, 2025)
This paper examines the rapid adoption of digital strategies in university education and management, viewing digital transformation as a strategic path for higher education. It explores dimensions of digital transformation, features of fourth-generation universities, and indicators of digital readiness and identity. Using a descriptive–analytical approach, the study reviews relevant literature and the initiatives of Algeria’s Ministry of Higher Education. Findings emphasize the need for a roadmap to guide digital transformation, highlighting universities’ central role as drivers of change, innovation, and progress in the sector.Jel Classification Codes: O33, I23, I28
Keywords: Keywords: Digital transformation, fourth-generation university, higher education in Algeria